Solución de la ecuación de Hamilton-Jacobi para el oscilador de Caldirola-Kanai - Pastrana-Arteaga, Leonardo; Segovia-Chaves, Francis Armando (Revista Científica, 2016)
The method allows Hamilton-Jacobi explicitly determine the generating function from which is possible to derive a transformation that makes soluble Hamilton's equations. Using the separation of variables the partial differential equation of the first order called Hamilton-Jacobi equation is solved; as a particular case consider the oscillator Caldirola-Kanai (CK), which is characterized in that the mass presents a temporal evolution exponentially . We demonstrate that the oscillator CK position presents an exponential decay in time similar to that obtained in the damped sub-critical oscillator, which reflects the dissipation of total mechanical energy. We found that in the limit that the damping factor is small, the behavior is the same as an oscillator with simple harmonic motion, where the effects of energy dissipation is negligible.